Well-being effects of the digital platform economy: the case of temporary and self-employment - Blázquez, Maite; Herrarte, Ainhoa; Moro-Egido, Ana I. (Technological and Economic Development of Economy, 2024)
The surge in non-traditional employment, including self-employment and temporary jobs, driven by the digital platform economy (commonly known as the gig economy), has thrust this form of work into the centre of social and political discussions. Among the European Union countries, Spain stands out with the highest volume of digital platform work. To explore the well-being effects of various gig economy employment arrangements, this study utilizes microdata from the Spanish Living Conditions Survey for 2018 and Google Trends data related to platforms like Deliveroo, Airbnb, Just Eat, Uber, and Freelance as a proxy for digital platform economy demand. Employing an econometric approach based on instrumental variables, the study reveals that the most detrimental well-being effects are observed among self-employed workers. Specifically, in terms of self-reported health, self-employed individuals (own-account workers) exhibit 125.8% lower average health levels compared to permanent workers. These findings suggest that the heightened job insecurity and precariousness associated with self-employment outweigh the potential benefits arising from greater flexibility and autonomy in this type of work. first published online 17 September 2024